Predictors of Malnutrition in Children Aged Less than 5 Years in Surabaya, Indonesia - Hidayat, Abdul Aziz Alimul; Prasetyo, Eko (Pakistan Journal of Nutrition, 2018)
Background and Objective: Malnutrition in children in the community is still a problem in Indonesia, especially in Surabaya. This study aimed to analyze the predictors of malnutrition in Surabaya, Indonesia. Methodology: The study used a cross-sectional design with 114 families with malnutrition, selected by proportionate stratified random sampling. The data were collected with questionnaires and interviews that identified underlying factors, while specifics about malnutrition were collected using weight-for-age measurements that were then assessed by Z score. Results: Factors of maternal education, maternal knowledge, family income and history of disease simultaneously affected 93.3% (adjusted R 0.933) of malnutrition variables in children. The strongest predictors of child malnutrition were family income (b = 0.265), followed by maternal education (b = 0.245), history of Infectious Diseases (b = 0.191) and maternal knowledge (b = 0.115). Conclusion: Malnutrition in children in Surabaya, Indonesia, could be overcome by improving family income, increasing the knowledge and education of mothers and preventing the existence of infectious diseases.